1982
DOI: 10.1159/000121579
|View full text |Cite
|
Sign up to set email alerts
|

Sea-Finding Behaviour of Loggerhead Hatchlings: The Time Course of Transient Circling Following Unilateral and Asynchronous Bilateral Blindfolding

Abstract: Marine turtle hatchlings orient seaward by responding to photic cues that guide them toward the brightest horizon. Earlier research has suggested that they have a positive phototropotactic reaction to light but the behaviour must be more complex than this because circling both toward the uncovered and the covered eye has been observed in unilaterally blindfolded turtles. The present work resolved some of these problems by studying circling direction as a function of how long one eye had been covered prior to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1985
1985
2004
2004

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…A fairer indication of poor orientation is that so many turtles did not traverse the arena within the 2 min. Unblindfolded turtles tested in similar circumstances nearly always travel this distance in a much shorter time and nearly always without making any circles (KINGSMILL 1980). Fig.…”
Section: Resultsmentioning
confidence: 86%
“…A fairer indication of poor orientation is that so many turtles did not traverse the arena within the 2 min. Unblindfolded turtles tested in similar circumstances nearly always travel this distance in a much shorter time and nearly always without making any circles (KINGSMILL 1980). Fig.…”
Section: Resultsmentioning
confidence: 86%
“…First, upon emerging from the nests, hatchlings use visual cues to orient towards the sea. Studies have shown that hatchling Loggerhead and Green Turtles exhibit a strong phototropotactic response, and will orient towards the brightest light in the vicinity, which, in the absence of artificial lights, is the horizon over the ocean, highlighted by the reflection of light off the ocean (Carr 1962;Kingsmill and Mrosovsky 1982;Mrosovsky and Kingsmill 1985;Salmon and Wyneken 1990;Peters and Verhoeven 1994) (Fig. 7).…”
Section: Homing and Orientation In Reptilesmentioning
confidence: 99%